Innovative Directions of Tourism Development - Mashhura Toirxonovna Alimova; Shirin Yakubovna Abdusaidova; Inoyatillo Ismatilloyevich Tuychiev (Universitas Muhammadiyah Sidoarjo, 2020)
In the article, the introduction of innovations in the field of tourism is considered as an important factor in the competitive world of the tourism market. The essence of innovation in this regard is revealed based on a theoretical analysis of the definitions given by this category of scientists. There are also presented directions of innovative development of the tourism sector through the application of information technologies in the field.